Progress in pediatric obesity: new and advanced therapies. Issue 4 (5th August 2022) - Cuda, Suzanne; Censani, Marisa
Abstract : Purpose of review: In this review, we discuss new medical and surgical options for the treatment of children and adolescents with obesity. We review the impact of COVID-19 on this vulnerable population. We also discuss the recent availability of screening tests for rare genetic causes of obesity. Recent findings: COVID-19 increased the prevalence of obesity among children and adolescents. This population is at increased risk for severe disease. The field of pediatric obesity has benefited from the approval of two new antiobesity medications: liraglutide and setmelanotide. We discuss indications for their use. New guidelines for surgical options for the treatment of children and adolescents with obesity are reviewed. These options are increasingly used as part of the comprehensive care for these children. Summary: The epidemic of childhood obesity continues. COVID-19 and the associated isolation contributed to the problem. However, promising new medical and surgical therapies and screening tests for rare genetic causes of obesity are available. These new diagnostic and therapeutic options bring renewed enthusiasm to the treatment of children and adolescents with obesity and increased recognition that obesity is a chronic disease starting in childhood deserving intervention to prevent consequences.